Liver biomarkers, genetic and lifestyle risk factors in relation to risk of cardiovascular disease in Chinese - Wang, Xinyu; Cheng, Si; Lv, Jun; Yu, Canqing; Guo, Yu; Pei, Pei; Yang, Ling; Millwood, Iona Y.; Walters, Robin; Chen, Yiping; Du, Huaidong; Duan, Haiping; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Liver biomarkers and metabolic associated fatty liver disease (MAFLD) have been shown to be associated with cardiovascular disease (CVD). However, there is limited evidence on CVD subtypes [myocardial infarction (MI), ischemic stroke (IS), and intracerebral hemorrhage (ICH)], especially in the Chinese population. We examined these associations overall, by genetic predisposition to non-alcoholic fatty liver disease (NAFLD), and by lifestyle risk factors. Approach and results This is a nested case-control study of CVD (10,298 cases and 5,388 controls) within the China Kadoorie Biobank. Cox regression was used to estimate adjusted hazard ratios (HRs) for CVD associated with liver biomarkers and MAFLD and by stratum of genetic risk and a combined high-risk lifestyle score. For liver enzymes, there were positive associations with MI and IS, but no associations with ICH or carotid plaque. There were positive associations of NAFLD with risks of MI, IS, and ICH (HR 1.43 [95% CI 1.30–1.57], 1.25 [1.16–1.35], and 1.12 [1.02–1.23]) as well as carotid plaque (odds ratio 2.36 [1.12–4.96]). The associations of NAFLD with CVD and carotid plaque were stronger among individuals with a high genetic risk (ICH: p-interaction < 0.05), while the associations with stroke were stronger among those with a favorable lifestyle (p-interaction < 0.05). The results for MAFLD mirrored those for NAFLD. Conclusion In Chinese adults, liver biomarkers and MAFLD were associated with risk of CVD, with different magnitudes of associations by CVD subtypes. Genetic predisposition to NAFLD and lifestyle factors modified the associations of fatty liver with stroke.